1976
DOI: 10.1007/bf00327708
|View full text |Cite
|
Sign up to set email alerts
|

Satellite DNA and evolution of sex chromosomes

Abstract: The satellite DNA (SATELLITE III) which is mainly represented in the female of Elaphe radiata (Ophidia, Colubridae) has been isolated and its buoyant density has been determined (delta equals 1.700 g cm-3). In situ hybridisation of radioactive complementary RNA of this satellite DNA with the chromosomes of different species has revealed that it is mainly concentrated on the W sex chromosome and its sequences are conserved throughout the sub-order Ophidia. From hybridisation studies these sequences are absent f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0
4

Year Published

1984
1984
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(98 citation statements)
references
References 23 publications
4
83
0
4
Order By: Relevance
“…(1971) and Singh et aL (1976Singh et aL ( , 1980. Singh et aL, (1976Singh et aL, ( , 1980 demonstrated that the heterochromatinisation of the W-chromosome in several snakes is correlated, at least in part, to the accumulation of a specific sex-linked satellite-DNA.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…(1971) and Singh et aL (1976Singh et aL ( , 1980. Singh et aL, (1976Singh et aL, ( , 1980 demonstrated that the heterochromatinisation of the W-chromosome in several snakes is correlated, at least in part, to the accumulation of a specific sex-linked satellite-DNA.…”
Section: Resultsmentioning
confidence: 98%
“…(1971) and Singh et aL (1976Singh et aL ( , 1980. Singh et aL, (1976Singh et aL, ( , 1980 demonstrated that the heterochromatinisation of the W-chromosome in several snakes is correlated, at least in part, to the accumulation of a specific sex-linked satellite-DNA. It is possible that there is also a W-linked highly repetitive DNA in Takydromus (and presumably also in other lizards) since the positive C-banding is known to depend on the presence of highly repetitive DNA sequences, often having the characteristics of satellite-DNA (John and Mikios, 1979).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Comparative studies from different reptiles have been interpreted as indicating that (gata)n/ (gaca)m sequences have been important in sex chromosome evolution. In many animals these sequences hybridize to the sex chromosomes carrying the largest amount ofheterochromatin (Singh et al 1976;Jones 1983). Here experimental evidence is presented that various simple repeats are implicated in the early stages of sex chromosome differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…A comparative analysis of sex-related sequences and chromosomes is perhaps the most tractable of these approaches, but it requires the initial identification of sex-related sequences. There are very few sex-specific sequences reported for reptiles (Cooper et al, 1997;Halverson and Spelman, 2002), although repetitive satellite sequences are known to be interspersed throughout the chromosomes of snakes in high copy number (Singh et al, 1976(Singh et al, , 1980 and are concentrated in particularly high density on the W chromosome (Solari, 1994). A number of functional genes have recently been mapped to the Z and W chromosomes of three snakes, a gecko and a turtle (Matsubara et al, 2006;Kawaia et al, 2007;Kawagoshi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%